ECONOMIC GROWTH AND PROSPERITY IN DIFFICULT CONDITIONS AT THE BEGINNING OF THE 21st CENTURY - Vladimir Gonda; Daria Rozborilova (European Scientific Journal, ESJ, 2014)
Beginning of the 21st century can be specified as a period characterized by the reversal in the direction of intensifying pessimistic expectations regarding the possibility of overcoming the consequences of the global financial and economic crisis in a relatively short timeframe. The complexity of the problem requires finding of the solutions in collaboration of scientists from different disciplines, as well as cooperation theorists and economic policy makers, particularly in their orientation on real resources and their effective use. The paper is based on the identification of problems related to the long term revaluation of the importance of economic growth, and underestimation of the importance of prosperity as well as the comparison of the values of indicators of economic growth and prosperity (the subject of our interest are the EU countries), in order to justify the need for modifications to their perception, specify their interdependence and identify the primary determinants that may play a positive role in ensuring sustainable economic growth rate, and to increase the level of prosperity in the current difficult conditions. Implementation objective entails the application of holistic approach.